2015
DOI: 10.1016/j.athoracsur.2015.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Resection of Multiple Müllerian Cysts

Abstract: Müllerian cysts in the mediastinum were first described by Hattori in 2005 [1]. We report the first known case of multiple müllerian cysts in the thorax in a 35-year-old woman with cough and an abnormal chest roentgenogram. Multiple bilateral cysts were resected thoracoscopically. Histologic examination showed benign ciliated tubal epithelium that stained positive with immunohistochemical stains for estrogen receptor (ER), cancer antigen 125 (CA-125), Wilms' tumor protein 1 (WT-1), and paired box gene 8 (PAX8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…Müllerian cysts commonly develop in the male pelvis, where the Müllerian duct is left behind, although female Müllerian cysts in the retroperitoneum and mediastinum have also been reported [ 3 ]. After the first report by Hattori in 2005 [ 1 ], until date, 25 cases of Müllerian cysts have been reported, including the present case [ 1 , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ]. The 25 reported cases of Müllerian cysts were reviewed for the site, size, and symptoms of the tumor.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Müllerian cysts commonly develop in the male pelvis, where the Müllerian duct is left behind, although female Müllerian cysts in the retroperitoneum and mediastinum have also been reported [ 3 ]. After the first report by Hattori in 2005 [ 1 ], until date, 25 cases of Müllerian cysts have been reported, including the present case [ 1 , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ]. The 25 reported cases of Müllerian cysts were reviewed for the site, size, and symptoms of the tumor.…”
Section: Discussionmentioning
confidence: 86%
“…The prognosis of this tumor is presumed to be good, with no reports of recurrence after surgical removal. However, a case of respiratory distress was reported due to multiple development and progression [ 13 ]. Most of the reported cases of a Müllerian cyst in the mediastinum required further diagnosis with resected tissue because preoperative diagnosis was difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of a posterior mediastinal Mullerian cyst is still not yet completely understood. Previous reported cases of Hattori's cysts have posited that such cysts are the result of remnant Mullerian tissue during embryogenesis as proposed by Ludwig et al in his study of Mayer-Rokitansky-Kuster syndrome [ 7 , 8 ]. The first Mullerian duct anlage arises in the 3rd to 5th thoracic vertebral blastema in stage 16 embryos.…”
Section: Discussionmentioning
confidence: 99%
“…It has been theorized that ectopic peritoneal cells undergo metaplasia into secondary Müllerian epithelium, or that Müllerian tissue is shed during the descent of the Müllerian ducts in embryogenesis. 3 It has previously been reported that the majority of cases occur in perimenopausal patients who frequently have a gynecological history. 2 Simmons and colleagues 4 were the first to report that these mediastinal cysts express paired box gene 8 and Wilms’ tumor 1, markers of Müllerian differentiation.…”
Section: Discussionmentioning
confidence: 99%